Numerical modelling of the aerodynamic interference between helicopter and ground obstacles - Chirico, G.; Vigevano, L.; Barakos, G.N. (My University, 2015)
Helicopters are frequently operating in confined areas where the complex flowfields that develop in windy conditions may result in dangerous situations. Tools to analyse the interaction between rotorcraft wakes and ground obstacles are therefore essential. This work, within the activity of the GARTEUR AG22 - "Forces on Obstacles in Rotor Wake", attempts to assess numerical models for this problem. In particular, a helicopter operating in the wake of a building, one main rotor diameter above the ground, has been analysed. Tests performed at Politecnico di Milano provide a basis for comparison to validate CFD solvers. Afterward, unsteady simulations have been performed, with and without external wind. The helicopter has been modeled as steady and unsteady actuator disk and fully resolved blade simulations have been carried out to evaluate the accuracy of those simpler models. The final goal is to find the more efficient aerodynamic model that captures the wakes interaction so that real time coupled simulations can be made. Previous studies have already proved that the wake superposition technique cannot guarantee accurate results if the helicopter is close to the obstacle. The validity of that conclusion has been investigated in this work to determine the minimum distance between helicopter and building at which minimal wake interference occurs.
Keywords: Aerodynamics